Evaluation of Nutmeg Flesh Extract as a Natural Anti-Acne Agent Against Cutibacterium acnes - Angga Saputra Yasir; Indah Puspita Sari; Indarto I; Sinta Bella Triyanti; Aida Febina Sholeha; Veni Putri Nurhayati (University of Jember, 2025)
Acne vulgaris is a common chronic inflammatory skin disorder primarily caused by Cutibacterium acnes infection. This study aims to investigate the phytochemical composition, total flavonoid content, and antibacterial activity of the ethanolic extract of Myristica fragrans fruit flesh against C. acnes and Staphylococcus aureus. The dried fruit flesh was extracted using ultrasonic-assisted ethanol extraction, followed by qualitative phytochemical screening and total flavonoid quantification via the aluminum chloride colorimetric method. Antibacterial activity was evaluated using the disc diffusion method at extract concentrations of 10%, 20%, and 30%, with standard antibiotics as positive controls. The extract contained key bioactive compounds including flavonoids, terpenoids, tannins, saponins, and alkaloids. Total flavonoid content averaged 0.15820 ± 0.00440 mg quercetin equivalent per gram of dry extract. The extract exhibited dose-dependent antibacterial effects, with more potent inhibition against C. acnes than S. aureus. Inhibition zones at 30% concentration reached notable diameters, confirming significant antibacterial activity based on CLSI standards. These findings highlight the potential of M. fragrans fruit flesh as a promising natural source of multifunctional bioactive compounds for anti-acne cosmeceutical development. Further studies involving compound isolation and in vivo efficacy testing are recommended to support its clinical application.